Avaliação da migração vertical de hidrocarbonetos policíclicos aromáticos (HPA) em solo agrícola condicionado com biocarvão - Moura, Hiago Rodrigues de (2020)
Polycyclic aromatic hydrocarbons (PAH) are formed in the environment, mainly by anthropogenic actions such as chemical substances and biomass burning and, when present in the soil, represent a risk to the health of animals and humans. Soil is the main destination of PAH and the presence of these compounds contributes to reduce each year the amount of arable land. One of the techniques used for the remediation of these compounds in the soil is the addition of biochar, a product formed through the biomass pyrolysis and that when used in the soil can immobilize polluting compounds, not allowing to reach groundwater reserves, and also allowing improving in its physical-chemical characteristics and increasing its fertility. Thus, the main objective of this study was to evaluate the influence of biochar from cattle manure and water hyacinth, produced through the pyrolysis of these biomasses at 500 ºC, in the vertical mobilization of PAH in agricultural soil. The result of identification and quantification of these compounds in the collected soil showed that only 5 of the 16 PAH listed by the US EPA as priority pollutants were found, in a total amount of 141.86 ng g-1. The total amounts of PAH in the leachate showed a reduction when the soil was conditioned with biochar of cattle manure and water hyacinth. The result also showed total amounts of PAH of 865.73 ng g-1 in bovine manure biochar and 785.24 ng g-1 in water hyacinth biochar. The total amounts of PAH in the soils containing the biochars were higher, including the appearance of PAH not previously quantified, indicating that this product may, in the long run, act as a source of PAH in the soil. The germination experiments show little influence of the biochar on the percentage and on the germination speed index, however, the plants germinated in the soil conditioned with bovine manure biochar show a reduction in the size of the roots, since they can exceed the PAH in the soil.